Combining the Liu-type estimator and the principal component regression estimator - İNAN, DENİZ (SPRINGER, 2015)
In this study a new two-parameter estimator which includes the ordinary least squares, the principal components regression (PCR) and the Liu-type estimator is proposed. Conditions for the superiority of this new estimator over the PCR, r-k class estimator and Liu-type estimator are derived. Furthermore the performance of this estimator is compared with the other estimators in different conditions with simulation studies.
Keywords: Liu-type estimator; r-k class estimators; Principal component regression estimator; Ridge estimator; Multicollinearity; RIDGE-REGRESSION